Inclusive sex education : narratives of good practice from Ireland and Sweden - Sherlock, Leslie (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2015)
Sex education for young people can take many forms and can promote diverse theoretical, political and social perspectives on sexuality and the body. The ways that sex education modalities function, the challenges they meet, the contextual circumstances they operate within and the discourses they put forward are varied and complex. School-based initiatives can be particularly politicised. Professionals who work in the area as researchers, facilitators and employees of government and society-based initiatives hold unique perspectives on the sex education milieu within their national context.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin